Reinventing the U.N a proposal - D'Escoto Brockmann, Miguel (Nicaragua | MANAGUA PAVSA, Managua, 2011)
The United Nations was created on June 26, 1945 as the best way to deal with the fear that, unless serious steps were taken, wars, such as the two world wars in the first half of the century, would continue to plague us. As we all know, that was a very good idea that did not work simply because, right from the very beginning, there were those who believed in wars of aggression, such as the ones we are witnessing today against Iraq, Afghanistan, and Libya, as a means of imposing their “full spectrum dominance” over the world, to use the phrase coined by the Pentagon itself
Sin Especificar
Idioma en Ingles
Keywords: Administración de justicia | Carta de la Organización de las Naciones Unidas | Derecho ambiental | Derecho internacional | Medio ambiente | Tribunal de justicia de las comunidades europeas